2020
DOI: 10.3390/coatings10010056
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Photoelastic Property and Stress Analysis for Optical Polyimide Membrane through Stress Birefringence Method

Abstract: Optical polyimide (PI) membranes have been increasingly attractive in optoelectronic substrate and optical element material applications. Controlled stress distribution is very important to optical PI membrane-based optics. However, nondestructive absolute stress measurement inside optical PI membranes remains challenging. In this letter, we adopted the stress birefringence method to experimentally investigate the correlation between stress and retardation in uniaxially, biaxially, and circularly stretched PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…First, a 100 nm thick gold reflector was deposited on a large-size PET membrane with a thickness of 4 μm using magnetron sputtering technology. Then, a large-size PET membrane was pre-tensioned using membrane tensioning ring [ 26 ], which is a method of applying pre-stress through mechanical stretching. The pre-tensioning force was applied to the PET membrane with a diameter of 68 mm.…”
Section: Fabrication and Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a 100 nm thick gold reflector was deposited on a large-size PET membrane with a thickness of 4 μm using magnetron sputtering technology. Then, a large-size PET membrane was pre-tensioned using membrane tensioning ring [ 26 ], which is a method of applying pre-stress through mechanical stretching. The pre-tensioning force was applied to the PET membrane with a diameter of 68 mm.…”
Section: Fabrication and Packagingmentioning
confidence: 99%
“…The way to apply tensile pre-stress to flexible polymer diaphragms is relatively simple. Due to the flexibility of the polymer diaphragm, the diaphragm tensile pre-stress can be applied by mechanical stretching [ 26 ]. Therefore, a GI acoustic sensor based on a flexible polymer diaphragm is proposed and experimentally demonstrated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The photoelastic method has been used to characterize the stress-optical properties of polymer films. Gao et al measured the stress-optical coefficients of optical polyimide (PI) films by uniaxial stretching experiments [29]. In particular, Lee et al calibrated the stress-optical coefficients of PET and PEN films in two orthogonal directions using the split-beam two-dimensional photoelastic technique, and the results showed that their stress-optical coefficients were different in the 0 • and 90 • directions [30].…”
Section: Introductionmentioning
confidence: 99%
“…The photoelastic method presents an advantage, compared to other experimental methods, that allows finding the whole stress field from the analysed specimen. Due to the advantages such as precision and rapidness, the photoelastic method continues to be one of the most effective methods for establishing the stress concentration factor [54][55][56][57]. The validation of a model can be obtained in two manners: qualitatively, by comparing the theoretical/numerical fields with the experimental ones provided by isochromatics (curves obtained for the constant difference between the normal principal stresses) [58,59], and quantitatively, by finding the complete stress tensor field; this requires finding, in addition to the isochromatic fields, the isoclinic fields (curves for which the directions of the principal stresses are the same) and the isopachic fields (curves for which the sum of the normal principal stresses is constant) [60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%